Postnatal Sox6 Regulates Synaptic Function of Cortical Parvalbumin-Expressing Neurons - Munguba, Hermany; Chattopadhyaya, Bidisha; Nilsson, Stephan; Carrico, Josianne N.; Memic, Fatima; Oberst, Polina; Batista-Brito, Renata; Munoz-Manchado, Ana Belen; Wegner, Michael; Fishell, Gordon; Di Cristo, Graziella; Hjerling-Leffler, Jens (Journal of Neuroscience, 2021)
Cortical parvalbumin-expressing (Pvalb(+)) neurons provide robust inhibition to neighboring pyramidal neurons, crucial for the proper functioning of cortical networks. This class of inhibitory neurons undergoes extensive synaptic formation and maturation during the first weeks after birth and continue to dynamically maintain their synaptic output throughout adulthood. While several transcription factors, such as Nkx2-1, Lhx6, and Sox6, are known to be necessary for the differentiation of progenitors into Pvalb(+) neurons, which transcriptional programs underlie the postnatal maturation and maintenance of Pvalb(+) neurons' innervation and synaptic function remains largely unknown. Because Sox6 is continuously expressed in Pvalb(+) neurons until adulthood, we used conditional knock-out strategies to investigate its putative role in the postnatal maturation and synaptic function of cortical Pvalb(+) neurons in mice of both sexes. We found that early postnatal loss of Sox6 in Pvalb(+) neurons leads to failure of synaptic bouton growth, whereas later removal in mature Pvalb(+) neurons in the adult causes shrinkage of already established synaptic boutons. Paired recordings between Pvalb(+) neurons and pyramidal neurons revealed reduced release probability and increased failure rate of Pvalb(+) neurons' synaptic output. Furthermore, Pvalb(+) neurons lacking Sox6 display reduced expression of full-length tropomyosin-receptor kinase B (TrkB), a key modulator of GABAergic transmission. Once re-expressed in neurons lacking Sox6, TrkB was sufficient to rescue the morphologic synaptic phenotype. Finally, we showed that Sox6 mRNA levels were increased by motor training. Our data thus suggest a constitutive role for Sox6 in the maintenance of synaptic output from Pvalb(+) neurons into adulthood.
CRIS-Team WoS Importer:2021-11-12